Healthcare delivery for paediatric and adolescent diabetes in low resource settings: Type 1 diabetes clinics in Uganda. - Bahendeka, Silver; Mutungi, Gerald; Tugumisirize, Florence; Kamugisha, Albert; Nyangabyaki, Catherine; Wesonga, Ronald; Sseguya, Wenceslaus; Mubangizi, Denis; Nalunkuma, Cissy; Were, Thereza Piloya (https://doi.org/10.1080/17441692.2019.1611897, 2019)
The management of type 1 diabetes (T1DM) includes setting up organised follow-up clinics. A programme for establishing such clinics in Uganda commenced in 2009. The clinics were established along the chronic care model and were integrated into the health structure of other chronic diseases. Web-based electronic medical records were utilised to establish a centralised registry. All children with diabetes below 18 years of age were encouraged to enrol into the programme by attending the nearest established T1DM clinic. At the commencement of the programme, there were 178 patients with T1DM receiving care in various health facilities but without organised follow-up T1DM clinics. These patients were subsequently enrolled into the programme and as of June 30, 2018, the programme had a total of 32 clinics with 1187 children; 3 with neonatal diabetes. Challenges encountered included difficulties in timely diagnosis, failure to provide adequate care in the remote rural areas and failure to achieve pre-defined glycated haemoglobin (HbA1c) goals. Despite these challenges, this observational study demonstrates that healthcare delivery for T1DM organised along the chronic care model and supported by web-based electronic medical records is achievable and provides care that is sustainable. Addressing the encountered challenges should result in improved outcomes for T1DM.
Keywords: Type 1 diabetes; Uganda; chronic care model; diabetes clinic; healthcare; low-income